Comparing Adherence of Continuous and Automatic Positive Airway Pressure (CPAP and APAP) in Obstructive Sleep Apnea (OSA) Children - Tovichien, Prakarn; Kulbun, Aunya; Udomittipong, Kanokporn (Frontiers in Pediatrics, 2022)
Objectives: The treatment outcomes of pediatric obstructive sleep apnea (OSA) are affected by positive airway pressure (PAP) therapy adherence, which may be affected by the type of device used. Continuous PAP (CPAP) devices deliver a continuous and fixed air pressure level, whereas automatic PAP (APAP) devices automatically adjust the pressure to meet changing needs during sleep. The adherence, tolerance and consistency of OSA-children’s use of CPAP and APAP devices were compared. Study design: One-year, observational cohort study Methods: Twenty-seven OSA-children were enrolled. Fourteen (52%) used CPAP, and 13 (48%) used APAP. The adherence, tolerance, and consistency of the PAP usage by the 2 groups were compared. Results: Overall, 11 of the 27 children (41%) showed good PAP adherence. The CPAP patients averaged 4.9 hours of device usage on the days used, for 60% of days, with 6 of 14 (43%) demonstrating good adherence. In comparison, the APAP patients averaged 3.2 hours for 55% of days, with 5 of 13 (38%) exhibiting good adherence. The 2 groups showed no differences in their adherence, tolerance, or consistency of device usage (P values, 0.609, 0.720, and 0.816, respectively). Although the adherence of both groups improved in the second six months, it was without statistical significance (P values, 0.400 and 0.724). Age, sex, baseline apnea-hypopnea index, comorbidities, prescribed period, device type, mask type, and caregiver education-level were not risk factors for poor PAP adherence. Conclusions: No differences in the adherence, tolerance, or consistency of the children’s use of CPAP and APAP were revealed in this small inhomogeneous cohort study with limited resources.